127k views
3 votes
Hi, I'm struggling with solving Linear equations and formula, e.g. 3(2x +y) =5y + 3 for Y? Can you assist me with the specific step to arrive at the answer? Thanks

1 Answer

4 votes

To solve


3(2x+y)=5y+3,

for y. First, we apply the distributive property on the left of the equation:


3\cdot2x+3y=5y+3.

Simplifying we get:


6x+3y=5y+3.

Now, we subtract 6x from the above equation:


6x+3y-6x=5y+3-6x\text{.}

Simplifying we get:


3y=5y-6x+3.

Subtracting 5y, we get:


\begin{gathered} 3y-5y=5y-6x+3-5y, \\ -2y=-6x+3. \end{gathered}

Finally, dividing by -2, we get:


y=(-6x+3)/(-2)=(6x-3)/(2)\text{.}

Answer:


y=(6x-3)/(2)\text{.}